2023
DOI: 10.1017/s026357472200176x
|View full text |Cite
|
Sign up to set email alerts
|

Broad learning control of a two-link flexible manipulator with prescribed performance and actuator faults

Abstract: In this paper, we present a broad learning control method for a two-link flexible manipulator with prescribed performance (PP) and actuator faults. The trajectory tracking errors are processed through two consecutive error transformations to achieve the constraints in terms of the overshoot, transient error, and steady-state error. And the barrier Lyapunov function is employed to implement constraints on the transition state variable. Then, the improved radial basis function neural networks combined with broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It is noted that the robot can be operated without the skill level of a human controller, making it an effective tool for minimally invasive surgery. Niu et al [106] suggested a broad learning control method for a two-link flexible manipulator with prescribed performance (PP) and actuator faults using a neural network-based adaptive dynamic programming algorithm. The broad learning theory combined with improved RBFNN was constructed in order to mimic the dynamics of flexible robotic manipulators' uncertain model.…”
Section: B Dual-linkmentioning
confidence: 99%
“…It is noted that the robot can be operated without the skill level of a human controller, making it an effective tool for minimally invasive surgery. Niu et al [106] suggested a broad learning control method for a two-link flexible manipulator with prescribed performance (PP) and actuator faults using a neural network-based adaptive dynamic programming algorithm. The broad learning theory combined with improved RBFNN was constructed in order to mimic the dynamics of flexible robotic manipulators' uncertain model.…”
Section: B Dual-linkmentioning
confidence: 99%